The Eurozone in Crisis: Diagnostic, Prospect, Reforms - Ponsot, Jean-François (2014)
The main argument of this article is that the foundations of the crisis in the Eurozone are much more complex than those expressed by the media and by economic analysts. The euro crisis is primarily the result of an incoherent and incomplete monetary and financial architecture. The euro as a single currency was set up with structural and institutional deficiencies that have not been corrected since its implementation: the euro is an incomplete currency. There are two radical options to save the European project: first, to transform the euro into a complete currency through fiscal federalism coupled with an industrial policy, a banking union and the implementation of transfer mechanisms; and second, to abandon the euro, in the event these reforms prove impossible.